1999
DOI: 10.1046/j.1365-2273.1999.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgery upon the quality of life in snoring patients and their partners: a between-subjects case-controlled trial

Abstract: Snoring is a common complaint in the community. Its psychosocial effect upon the relationship between sleeping partners is not known. This study examines prospectively by detailed tailored questionnaires the differences in the physical, psychological and social aspects in 27 snoring patients and their partners presenting to a snoring clinic and compares them with a control group of 24 patients who had undergone successful Laser-Assisted Uvulopalatoplasty (LAUP) and their partners. All areas examined showed imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 24 publications
1
24
0
1
Order By: Relevance
“…Habitual loud snoring may result in couples choosing to sleep apart or resort to using earplugs to counteract the sound [14]. These aspects can have a negative impact on the psychosocial aspects and the intimacy in a couple’s relationship, and even may trigger marital disharmony or result in divorce [1]. …”
Section: Introductionmentioning
confidence: 99%
“…Habitual loud snoring may result in couples choosing to sleep apart or resort to using earplugs to counteract the sound [14]. These aspects can have a negative impact on the psychosocial aspects and the intimacy in a couple’s relationship, and even may trigger marital disharmony or result in divorce [1]. …”
Section: Introductionmentioning
confidence: 99%
“…However, they did not present any significant improvement after 1 month of patients' CPAP therapy [18]. On the other hand, the study by Armstrong demonstrated a significant improvement in the quality of life in both patients and their partners after successful surgery for simple snoring [19]. Most previous studies focused on the [3-6, 18, 19].…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, CPAP use is lower among patients in whom seeking treatment is initiated by partners [22]. As in the group of mild-to-moderate OSAHS, the use of CPAP is rather controversial, and surgical treatment may provide considerable benefits for the patients' psychological condition as well as for their bed partners [8,19,23,24].…”
Section: Discussionmentioning
confidence: 96%
“…The noise of snoring can cause signifi cant marital and social problems and lead to sleep deprivation for the sleep partner. 1 Sleep apnoea, or more specifi cally obstructive sleep apnoea (OSA), is a more serious problem as the apnoeic episodes lead to reduced blood oxygen saturation and cardiovascular problems (particularly hypertension) in the long term. 2 OSA also causes signifi cant daytime sleepiness, with impaired daytime functioning and increased risk of road traffi c accidents.…”
Section: Introductionmentioning
confidence: 99%